Achievement for All / Working with Children with Special Educational Needs in Mainstream Schools and Colleges - Grant Julie (ATL - The Education Union, 2002)
Introduction, Cognition and Learning, Sensory and Physical Impairments, Communication and Interaction, Behaviour and Emotional and Social Development, Gifted and Talented Children, Special Educational Needs and Children with English as an Additional Language, Portage, Information and Communications Technologyand Special Educational Needs, The Role of Special Educational Needs Co-ordinators (SENCos), Useful Organizations, The Association of Teachers and Lecturers, Special Educational Needs Committee, Appendices.